Aptasensors for Staphylococcus aureus Risk Assessment in Food - Huang, Ziqian; Yu, Xin; Yang, Qingli; Zhao, Ying; Wu, Wei (Frontiers in Microbiology, 2021)
Staphylococcus aureus (S. aureus) is the top ordinary pathogen causing epidemic and food poisoning. The authentication of S. aureus has great significance for pathologic diagnosis and food hygiene supervision. Various biosensor methods have been established for identification. This paper reviews the research progress of aptasensors for S. aureus detection, focused on the classification of aptamer technologies, including optical aptasensors and electrochemical aptasensors. Furthermore, the feasibility and future challenges of S. aureus detection for aptamer assays are discussed. Aptasensors of nanomaterials are the developing direction of aptasensor.